Proposed SWOT Strategy with Attention to The Managerial Innovation Level - Roland Y.H. Silitonga; Bernardus Rizky (The Indonesian Institute of Science and Technology Research, 2022)
PT Sumber Inti Pangan is a spice and seasoning manufacturing industry that has continued to grow until now. The company's three-year trend of rising sales provides evidence of this growth. Since 2017, there has been an average growth in the consumption of spices and seasonings, according to rising sales trends and data on public consumption. The increase in average consumption and market opportunities trigger competition between companies. Companies must prepare, create, and obtain new sustainable products to compete. Managerial innovation has the potential to innovate products. In this study, SWOT analysis is used to propose long-term strategies that can help companies maximize strengths and opportunities and minimize weaknesses and threats. Managerial innovation analysis with the Fuzzy AHP method is used to analyze internal factors in the form of company strengths and weaknesses. Therefore, SWOT weaknesses that are still too broad, not detailed, and cannot prioritize the identified factors can be covered. On the other hand, PEST and Porter's Five Forces are used to analyze external factors in the form of opportunities and threats to the company. The results showed that the company's innovation rate was 52.262%. The company had innovated in the planning, leading, and controlling functions but could not innovate in the organizing and coordinating processes. Several strategies the company can utilize are conducting regular evaluations to get more innovative substitute products, adding organizational groupings based on customer base, and making annual plans.